PENGARUH SENAM JANTUNG SEHAT TERHADAP TEKANAN DARAH PASIEN HIPERTENSI ANGGOTA PROLANIS PUSKESMAS KUMEEMBUAI DI DESA KUMELEMBUAI - Marlinda Liando; Beatrix Podung; Vera Tombokan (Yayasan Syalom Cipta Sumikolah, 2024)
Hypertension is a condition that is often found in primary health care. The high incidence of hypertension is influenced by various factors, one of which is the activity factor. Physical activity is able to show a reduction in the risk of death by 29% to 67% in patients who do high levels of physical activity, and as much as 12% to 35% in patients who do moderate levels, this reflects that there is a relationship between the level of physical activity and a decrease in the risk of death in hypertensive patients. Healthy heart gymnastics is one of the gymnastic methods arranged to always prioritize the ability of the heart, large muscle movements and joint flexibility, in order to optimally incorporate oxygen into the body so that the body's oxygen needs are met. The type of research used is observational research using quantitative research methods with a one group pretest-postest approach research design with a sample size of 42 respondents conducted on February 22 - March 22, 2023. Based on the results of the study, it was found that there was an effect of healthy heart exercises on the blood pressure of hypertensive patients with prolanis members with a systolic p value = (0.000 <a = 0.05) and a diastolic p value = (0.000 <a = 0.05).